2022
DOI: 10.1111/gcb.16313
|View full text |Cite
|
Sign up to set email alerts
|

New tree‐level temperature response curves document sensitivity of tree growth to high temperatures across a US‐wide climatic gradient

Abstract: Temperature is a key climate indicator, whose distribution is expected to shift right in a warming world. However, the high-temperature tolerance of trees is less widely understood than their drought tolerance, especially when it comes to sub-lethal impacts of temperature on tree growth. I use a large data set of annual tree ring widths, combined with a flexible degree day model, to estimate the relationship between temperature and tree radial growth. I find that tree radial growth responds non-linearly to tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Though temperature mediated the ecohydrological transition in this system, different climatic factors likely drive transitions among other ecohydrological classes that emerge across larger spatial scales (Babst et al, 2019;Gantois, 2022;Roebroek et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Though temperature mediated the ecohydrological transition in this system, different climatic factors likely drive transitions among other ecohydrological classes that emerge across larger spatial scales (Babst et al, 2019;Gantois, 2022;Roebroek et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In California's White Mountains, for example, which are drier than the Sierra Nevada, only trees growing within 60–80 m of treeline were positively correlated with temperature (Salzer et al, 2014). In addition, a recent study suggested that tree growth‐temperature inflection points vary dramatically within the United States (i.e., ranging between 10°C and 30°C; Gantois, 2022). Species traits, as well as other ecohydrological classes, may be leading to highly variable temperature inflection points across large geographic gradients (Roebroek et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In theory, drought adaptations could occur at the scale of individuals (e.g., phenotypic plasticity) or local communities (e.g., tree density) or through evolutionary processes that occur across generations. Recent research, however, suggests that most climate adaptation develops over longer timescales than an individual tree’s life span ( 54 ). This suggests that genetic adaptation is an important mechanism that protects trees from climate change, but it also highlights the risk that rapid warming may outpace the rate of adaptation.…”
Section: Discussionmentioning
confidence: 99%